TOI-3884 b: A rare 6-R Eplanet that transits a low-mass star with a giant and likely polar spot - Almenara, J. M. (2022)
The Transiting Exoplanet Survey Satellite mission identified a deep and asymmetric transit-like signal with a periodicity of 4.5 days orbiting the M4 dwarf star TOI-3884. The signal has been confirmed by follow-up observations collected by the ExTrA facility and Las Cumbres Observatory Global Telescope, which reveal that the transit is chromatic. The light curves are well modelled by a host star having a large polar spot transited by a 6-RE planet. We validate the planet with seeing-limited photometry, high-resolution imaging, and radial velocities. TOI-3884 b, with a radius of 6:00 0:18 RE, is the first sub-Saturn planet transiting a mid-M dwarf. Owing to the host star's brightness and small size, it has one of the largest transmission spectroscopy metrics for this planet size and becomes a top target for atmospheric characterisation with the James Webb Space Telescope and ground-based telescopes.